2014
DOI: 10.1177/1533317514531442
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Cognitive Impairment in Patients With Parkinson’s Disease From India

Abstract: Depression and cognitive impairment are frequent manifestations in Parkinson's disease (PD). Although a few longitudinal studies have reported on depression and dementia in PD, there is a yet a lack of such studies in India. This 7-year longitudinal study is a hospital-based prospective case (n = 250)-control (n = 280) study. In all, 36.8% had PD with no cognitive impairment (PD-Normal), 27.2% of the patients with PD were affected by dementia (PDD), and 36% of the remaining patients with PD had mild cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
12
0
1
Order By: Relevance
“…The second new outcome was disease-specific; namely that living with dementia and diabetes increased the risk for severe hypoglycemia compared with persons living with diabetes and without dementia (Abbatecola et al , 2015; Prinz et al , 2015). Fourteen new articles (Chang et al , 2012; Chen et al , 2014; Huijts et al , 2013; Llibre et al , 2014; Katsoulis et al , 2014; Lee et al , 2015; Mignardot et al , 2014; Murao et al , 2014; O’Donnell et al , 2012; Park et al , 2016; Sanyal et al , 2014; Warchol-Celinska et al , 2015; van Asch et al , 2013) fell into existing chronic condition-outcome pairings and did not change the quality or strength of the evidence, and four articles (Hawkins et al , 2012; Jacobs et al , 2012; Hajduk et al , 2013; Provencher et al , 2015) were found in separate areas where there was previously no evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The second new outcome was disease-specific; namely that living with dementia and diabetes increased the risk for severe hypoglycemia compared with persons living with diabetes and without dementia (Abbatecola et al , 2015; Prinz et al , 2015). Fourteen new articles (Chang et al , 2012; Chen et al , 2014; Huijts et al , 2013; Llibre et al , 2014; Katsoulis et al , 2014; Lee et al , 2015; Mignardot et al , 2014; Murao et al , 2014; O’Donnell et al , 2012; Park et al , 2016; Sanyal et al , 2014; Warchol-Celinska et al , 2015; van Asch et al , 2013) fell into existing chronic condition-outcome pairings and did not change the quality or strength of the evidence, and four articles (Hawkins et al , 2012; Jacobs et al , 2012; Hajduk et al , 2013; Provencher et al , 2015) were found in separate areas where there was previously no evidence.…”
Section: Resultsmentioning
confidence: 99%
“…The point prevalence of dementia in PD was similar to previous epidemiological studies; one recent systematic review including 13 studies found that 31.3% of PD patients had dementia . Another study in India showed that 27.2% of PD patients had dementia and 36.8% of patients had MCI at baseline . In Italy, MCI was found in approximately 53% of 290 PD patients .…”
Section: Discussionmentioning
confidence: 98%
“…The progression rate from PD-MCI to PD dementia (PD-D) varies depending on age, disease duration and other factors, but one study found it to be approximately 60% over 4 years (Janvin et al, 2006). Other studies found it to be 45–60% while following up for 4–12 years (Buter et al, 2008) and a 49.28% prevalence rate for dementia over 7 years (Sanyal et al, 2014). …”
Section: Introductionmentioning
confidence: 94%